New bryozoan taxa from a new marine conservation area in New Zealand, with a checklist of Bryozoa from Greater Cook Strait - Gordon, Dennis P. (Zootaxa, 2009)
Seven new species of cheilostome Bryozoa are described from the new Taputeranga Marine Reserve on the south coast of Wellington City, New Zealand. Four of them [Catenicella pseudoelegans (Catenicellidae), Celleporina wellingtonensis and Osthimosia sirena (Celleporidae), and Reteporella aurantiaca (Phidoloporidae)] were discovered during a month-long “BioBlitz” to determine aspects of the biodiversity of the Marine reserve ahead of its official gazetting and are so far known only from the marine reserve. The remaining species [Electra oligopora (Electridae), Fenestrulina littoralis (Microporellidae), and Rhynchozoon zealandicum (Phidoloporidae)] occur both in the reserve and elsewhere on the New Zealand coast and this paper resolves long-standing taxonomic problems concerning their status, each of the three having previously been attributed to other species. All seven occur in the littoral zone, some extend into deeper water, and all are apparently endemic. With the addition of the new species, the bryozoan fauna of Greater Cook Strait comprises 232 species (13 undescribed/undetermined) and, for the New Zealand Exclusive Economic Zone, 953 marine species (of which 331 remain undescribed or undetermined).